(untitled) (Bioagro, 2025)
Cattails in Peruvian sector of Titicaca Lake, is still used as human food, so it is necessary to know its nutritional qualities and potential, therefore, it is proposed to characterize its nutritional composition and ethnobotanical value. Proximal analyses of basal stems, rhizomes and rhizomatic shoots ("chullu", "siphi" and "saka" respectively, by their local names of the edible parts) were carried in six replicates each and three for mineral analysis (Fe, P, K, Ca and I) under UV/VIS spectrophotometry and volumetric analisys; in addition, 45 people from communities surrounding Titicaca were interviewed, to know basic aspects of its ethnobotanical importance. Chullu and saka presented similar humidity levels (93,17 % and 92,87 %) and significantly lower in siphi (75,89 %); all of them had high ash contents (6,04 to 9,85%), chullu and saka were rich in fiber (22,59 % and 20,87 %) and siphi was high in carbohydrates (65,91 %), all three had moderate protein levels (6,97 to 10,44%). Siphi prevailed in calcium and iron contents (12,38 and 1,57 mg·(100 g)-1 respectively), high iodine concentrations were noted in the three organs, reaching 271,33 mg.(100g)-1 in siphi, higher than any conventional food. Almost 100 % of residents stated that they knew cattail as food for humans, with the highest report of use for chullu (65,08 %) and the lowest for siphi (12,70 %). Due to its nutritional qualities and ethnobotanical value, S. californicus represents an important alternative as a non-conventional food resource.